Potential of using ICT in Islamic-based education. - Nizam, Anis Adma; Omar, Nurfarhana; Sharin, Nur Hafazah; Ab Kadir, Nor Adila Hanim; Abdul Halim, Siti Sarah; Muhammad, Muhd. Rosydi (IIUM Press, 2011)
The advancement of Information Communication Technology (ICT) nowadays gives a great challenge to educators in order to continuously play significant roles in the borderless globalization of information era. This challenge should not be regarded as a threat but should be accepted as a great reward to education world. Thus, the main purpose of this paper is to discuss the potentials of using ICT in Islamic-based education and learning processes. In Islam, the use of modern technology is encouraged as it helps towards the development of positive thinking, the ability to innovate and to trigger the drive for self-improvement. Hence, in order to identify and promote ways in which ICT can enhance the reach and quality of Islamicbased education, this paper has focus how ICT can make the Islamic Studies courses is very interesting and entertaining and it can be proven that it is not impossible to transform a dry and plain subject to be fun and interactive lesson.